2016
DOI: 10.1093/molbev/msw044
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes of Plant Gametophytes Have a Higher Proportion of Rapidly Evolving and Young Genes than Sporophytes

Abstract: Reproductive traits in plants tend to evolve rapidly due to various causes that include plant-pollinator coevolution and pollen competition, but the genomic basis of reproductive trait evolution is still largely unknown. To characterize evolutionary patterns of genome wide gene expression in reproductive tissues in the gametophyte and to compare them to developmental stages of the sporophyte, we analyzed evolutionary conservation and genetic diversity of protein-coding genes using microarray-based transcriptom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 65 publications
8
33
1
Order By: Relevance
“…3A and Tables S2 and 3 ). This is consistent with previous studies, which reported that young genes tend to contribute more to the transcriptomes of the reproductive tissues compared with the old genes 14 , 16 . Cui, et al .…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…3A and Tables S2 and 3 ). This is consistent with previous studies, which reported that young genes tend to contribute more to the transcriptomes of the reproductive tissues compared with the old genes 14 , 16 . Cui, et al .…”
Section: Resultssupporting
confidence: 93%
“…3C ; Figure S2A,C and E , Table S4 , 5 , 6 , 7 , 8 , 9 , 10 and 11 ). This pattern is also consistent with previous studies, which reported that plant reproductive tissues tend to have more divergent transcriptomes and less selective pressure 4 , 14 , 16 . But the order of the transcriptomes divergence in the seedling and root is opposite that observed by Yang and Wang, though that could be because of different methods used to estimate the expression divergence and the use of only a single accession of A. thaliana 4 .…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations